A AC-DC converter/ wind turbine harmonic-free interface - Lee, Edwin Poh Chong (2016)
Wind turbine system has become a popular source of clean energy system. The global cumulative wind power capacity hit new recorded high level of 369, 553 MW in year 2014, 38.5% of those wind power facility are located in Asia. Wind energy conversion system converts kinetic energy into mechanical energy driving generator and eventually producing electricity. Variable output power is generated due to variable nature of wind, thus it is not suitable for connection into power grid. Hence, power converter system is installed at the generation side in order to match the frequency, phase and output voltage level of the grid. However, the used of power converter may potentially reduces life span of component and leading to drop in system’s efficiency by introduces high intensity of harmonics into the system. In this final year project report, I focused on designing and simulating a power converter circuit that can deliver stable output voltage and current while the input is fluctuating within controlled range, the other objective is to have harmonics free output with near unity power factor. Protection circuit, active and reactive power control is not our primary focus in this project. I have modelled and simulated the wind generation system with PSIM version 8.0 software. A standard 3-phase variable power source is used to represent input power that generated by wind turbine generator. AC/DC/AC converter system is utilized for conversion of variable input voltage and current into desired output. Two isolated loads are connected for fine tuning and investigation of power system’s output power factor and level of total harmonics distortion.